A Port Management Model in the Industrial Revolution 4.0 Era - Siti Hajar Aswad; Eka Djunarsjah (Jurnal Sosioteknologi, 2022)
Sedimentation is a natural and physical phenomenon that affects port management. Ifit is further elaborated, the main aspects of port management include planning, design,construction, and maintenance activities. To understand the effect of sedimentationon port management, a comparative study was conducted between the terms of portmanagement which are stated in the regulations that apply in Indonesia and theimplementation that has been carried out. realized at Patimban port. The purpose ofthe study to investigate the effects of sedimentation on port management activities isto formulate and give technical recommendations in the spatial and temporal contextthat need to be implemented by the port authorities. This recomendation must be donein a routine and timely manner, by integrating temporal change data with IndustrialRevolution 4.0-based technologies to increase the rate of data renewals, so that themanager of the port can respond to any changes that occur in the port accordingly andeffectively in a short period of time.